Cold Extrusion but Not Coating Affects Iron Bioavailability from Fortified Rice in Young Women and Is Associated with Modifications in Starch Microstructure and Mineral Retention during Cooking. Issue 12 (18th October 2017) - Hackl, Laura; Speich, Cornelia; Zeder, Christophe; Sánchez-Ferrer, Antoni; Adelmann, Horst; de Pee, Saskia; Tay, Fabian; Zimmermann, Michael B; Moretti, Diego
Abstract: Background: Rice can be fortified with the use of hot or cold extrusion or coating, but the nutritional qualities of the resulting rice grains have never been directly compared. Objective: Using fortified rice produced by coating or hot or cold extrusion, we compared 1 ) iron and zinc absorption with the use of stable isotopes, 2 ) iron and zinc retention during cooking, and 3 ) starch microstructure. Methods: We conducted 2 studies in young women: in study 1 [ n = 19; mean ± SD age: 26.2 ± 3.4 y; body mass index (BMI; in kg/m 2 ): 21.3 ± 1.6], we compared the fractional iron absorption (FAFe) from rice meals containing isotopically labeled ferric prophosphate ( 57 FePP), zinc oxide (ZnO), citric acid, and micronutrients fortified through hot extrusion (HER1) with rice meals fortified through cold extrusion containing 57 FePP, ZnO, citric acid, and micronutrients (CER); in study 2 ( n = 22; age: 24 ± 4 y; BMI: 21.2 ± 1.3), we compared FAFe and fractional zinc absorption (FAZn) from rice meals fortified through hot extrusion (HER2) compared with rice meals fortified through coating containing 57 FePP, ZnO, a citric acid and trisodium cirate mixture (CA/TSC), and micronutrients (COR) relative to rice meals extrinsically fortified with ferrous sulfate (reference). Rice types HER1 and CER contained citric acid, whereas types HER2 and COR contained CA/TSC. We assessed retention during standardized cooking experiments and characterized the rice starch microstructure. Results: FAFe (95% CI) was greater from CER [2.2% (1.4%, 3.4%)] than from HER1 [1.2% (0.7%, 2.0%)] ( P = 0.036). There was no difference in FAFe between HER2 [5.1% (3.7%, 7.1%)] and COR [4.0% (2.9%, 5.4%)] ( P = 0.14), but FAFe from COR was lower than that from the reference meal [6.6% (4.9%, 9.0%)] ( P = 0.003), and the geometric mean FAZn (95% CI) did not differ between HER2 [9.5% (7.9%, 11.6%)] and COR [9.6% (8.7%, 10.7%)] ( P = 0.92). Cooking in a rice-to-water ratio of 1:2 resulted in iron and zinc retentions >80%, and cooking in excess water did not affect iron retention from hot-extruded rice but caused iron losses of 25% from CER and COR. Distinct variations in starch microstructure were found in CER and HER1. Conclusions: Iron absorption was 64% higher from CER than from hot-extruded rice, with no difference between COR compared with hot-extruded rice. Lower extrusion temperatures may generate a more readily digestible starch structure, allowing for greater iron release in vivo but lower mineral retention during cooking. This trial was registered at clinicaltrials.gov as NCT02176759.